2009
DOI: 10.1111/j.1365-2567.2009.03048.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony‐stimulating factor‐induced immature myeloid cells inhibit acute graft‐versus‐host disease lethality through an indoleamine dioxygenase‐independent mechanism

Abstract: Please cite this article in press as: Joo Y.-D. et al. Granulocyte colony-stimulating factor-induced immature myeloid cells inhibit acute graft-versus-host disease lethality through an indoleamine dioxygenase-independent mechanism, Immunology (2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
(73 reference statements)
4
30
0
Order By: Relevance
“…Immature myeloid cells have been reported to be mobilized from bone marrow into peripheral blood primarily by G-CSF (70)(71)(72)(73)(74), which corroborates our finding that G-CSF, but not GM-CSF, KC, MIP-2, or MCP-1, acts as a critical proinflammatory molecule in MDL-1-induced shock by promoting the mobilization (and possibly the generation, egression, and maturation) of the pathogenic cells to the liver. In addition to the liver, these ring cells are also found in peripheral blood in response to ConA treatment (Supplemental Figure 7A), supporting the notion that immature myeloid cells egress from the bone marrow into the circulatory system in response to inflammation.…”
Section: Figuresupporting
confidence: 80%
“…Immature myeloid cells have been reported to be mobilized from bone marrow into peripheral blood primarily by G-CSF (70)(71)(72)(73)(74), which corroborates our finding that G-CSF, but not GM-CSF, KC, MIP-2, or MCP-1, acts as a critical proinflammatory molecule in MDL-1-induced shock by promoting the mobilization (and possibly the generation, egression, and maturation) of the pathogenic cells to the liver. In addition to the liver, these ring cells are also found in peripheral blood in response to ConA treatment (Supplemental Figure 7A), supporting the notion that immature myeloid cells egress from the bone marrow into the circulatory system in response to inflammation.…”
Section: Figuresupporting
confidence: 80%
“…On the other hand, it is known that, despite the approximately 1-loghigher T-cell content of G-CSF-mobilized PBSC grafts relative to conventional BM grafts, the use of G-CSF-mobilized PBSC grafts is not associated with an amplification of acute GVHD. 36 In fact, it has been reported that---in analogy with data in mice 31 ---systemic treatment with G-CSF induces an expansion of myeloid cells with in vitro T-cell suppressive activity; these have so far been broadly characterized as 'suppressive CD14 þ monocytes' 37 or 'activated granulocytes'. 38 Myeloid regulatory cells contained within the G-CSF-mobilized stem cell grafts may control the alloreactivity of donor T cells in the post-transplant period and thereby may contribute to the regulation of GVHD after this type of allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that exogenous administration of CpG and G-CSF induces CD11b þ Gr-1 þ MDSC in mice that, upon adoptive transfer into secondary recipients, can suppress GVHD. 14,31 Having previously shown that chimerism induction in radiation and F1 chimeras is associated with an endogenous expansion of CD11b þ Gr-1 þ myeloid suppressor cells, 18,19 we now show that these comprise typical MO and PMN CD11b þ Gr-1 þ MDSC subsets, both capable of suppressing in vitro and in vivo T-cell alloresponses. In the current study, we document this in a parent-in-F1 model, where chimerism is induced using parental splenocyte infusions, and we specifically chose this model so as to exclude any interference of conditioning-induced inflammation with the function of MDSC.…”
Section: Discussionmentioning
confidence: 99%
“…gMCs were isolated using previously described methods [10]. Briefly, B6 donor mice were subcutaneously (s.c) injected with recombinant human G-CSF (10 g) daily for 5 days.…”
Section: Isolation Of Cells Microarray and In Vitro Stimulationmentioning
confidence: 99%
“…gMCs are identified by CD11b + Gr-1 + and have an immature phenotype. The suppressive activity of gMCs is independent of indoleamine 2,3-dioxygenase (IDO) production [10]. In addition to their immune modulation activity, G-CSF-mobilized myeloid cell types have been reported to contribute to accelerated hematopoietic recovery after transplantation.…”
Section: Introductionmentioning
confidence: 99%